2018
DOI: 10.1002/ejic.201701341
|View full text |Cite
|
Sign up to set email alerts
|

RuII–Carbonyl photoCORMs with N,N‐Benzimidazole Bidentate Ligands: Spectroscopic, Lysozyme Binding Affinity, and Biological Activity Evaluation

Abstract: The photoinduced carbon monoxide releasing properties of pyridylbenzimidazole-based Ru II -carbonyl complexes functionalized with alkylated sulfonate (L SO3H ), phthalimide (L Phth ), and morpholine (L morph ) moieties, [RuCl(CO) 3 L SO3H ]Cl (1) and [RuCl 2 (CO) 2 L] {where L = L Phth (2) and L morph (3)}, are reported. The geometrical stereochemistry and electronic transitions are assigned with the aid of DFT and TDDFT calculations. The compounds are evaluated for potential antimicrobial and [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
3
16
0
Order By: Relevance
“…Moreover, under the same experimental conditions, the commercially available drugs cisplatin (IC 50 = 1.1 ± 0.2 μ m ) and carboplatin (IC 50 = 10 ± 1 μ m ) exhibit cytotoxic activity in the same order of magnitude as the newly synthesized compound . Similarly, previous studies of copper‐based complexes containing benzimidazole derivatives have demonstrated that the antineoplastic potential of benzimidazoles enhance upon copper(II) coordination …”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Moreover, under the same experimental conditions, the commercially available drugs cisplatin (IC 50 = 1.1 ± 0.2 μ m ) and carboplatin (IC 50 = 10 ± 1 μ m ) exhibit cytotoxic activity in the same order of magnitude as the newly synthesized compound . Similarly, previous studies of copper‐based complexes containing benzimidazole derivatives have demonstrated that the antineoplastic potential of benzimidazoles enhance upon copper(II) coordination …”
Section: Resultssupporting
confidence: 62%
“…[55] Similarly, previous studies of copper-based complexes containing benzimidazole derivatives have demonstrated that the antineoplastic potential of benzimidazoles enhance upon copper(II) coordination. [3,[5][6][7]10] Furthermore, as the ligand dppb presents certain planarity because the pyridine and the benzimidazole ring systems are almost coplanar, [49] it is interesting to investigate the interactions of its copper complex with DNA. For most copper(II) complexes, which act as antiproliferative agents, DNA binding is a crucial step for DNA cleavage and fragmentation.…”
Section: Cytotoxic Activity and Dna Binding Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2‐(2′‐pyridyl)benzimidazole ligands functionalized with morpholine (L morph ) and phthalimideo (L phth ) were synthesized following the published procedures . Manganese pentacarbonyl bromide was received from Strem chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…The functionalized morpholine (L morph ) and phthalimide (L phth ) ligands based on 2-(2′-pyridyl) benzimidazole were synthesized following the previously published method. [32] Heating to reflux the 1:1 (M: L) reaction mixture of manganese(I) pentacarbonyl bromide and the corresponding ligand yielded fac-[MnBr (CO) 3 L] (L = L morph (1) and L phth (2)) (Scheme 1). The complexes were characterized by elemental analysis, ESI-MS, IR and NMR ( 1 H, 13 C NMR, { 1 H, 1 H} COS90, and { 1 H, 13 C} HSQC) ( Figure S1-3).…”
Section: Synthesis Of Ligands and Complexesmentioning
confidence: 99%